2011
DOI: 10.1177/002204261104100305
|View full text |Cite
|
Sign up to set email alerts
|

Race/Ethnicity, Coping, and Drinking Outcomes

Abstract: Particular coping strategies involving behavioral and psychological responses to stressors are viewed as protective in relation to harmful effects of stressors, including problematic drinking. One framework for examining modes of coping has classified responses into those deemed either protective of or detrimental to health. This study examined racial/ethnic differences in the use of nine coping strategies and their relation to problematic drinking. Using two waves of data from a study of university employees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…White respondents appeared to be more likely to employ active coping strategies (3.87 versus 3.39), acceptance (4.24 versus 3.82) and self-blame (2.87 versus 2.26) coping strategies than AI respondents, while AI students were more likely to employ denial as a coping strategy than whites (1.66 versus 1.30). The finding that whites were more likely to employ active coping strategies is consistent with the notion that minorities, due to the increased likelihood of having limited resources (relative to whites), are less likely to engage in active coping strategies because of the resource demands needed to utilize such strategies (Richman et al, 2011). Overall, these results suggested that while some racial differences in the use of various coping strategies existed, there was considerable convergence in the use of various coping styles as well.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…White respondents appeared to be more likely to employ active coping strategies (3.87 versus 3.39), acceptance (4.24 versus 3.82) and self-blame (2.87 versus 2.26) coping strategies than AI respondents, while AI students were more likely to employ denial as a coping strategy than whites (1.66 versus 1.30). The finding that whites were more likely to employ active coping strategies is consistent with the notion that minorities, due to the increased likelihood of having limited resources (relative to whites), are less likely to engage in active coping strategies because of the resource demands needed to utilize such strategies (Richman et al, 2011). Overall, these results suggested that while some racial differences in the use of various coping strategies existed, there was considerable convergence in the use of various coping styles as well.…”
Section: Resultssupporting
confidence: 79%
“…Specifically, self-distraction appeared to be effective at reducing the propensity to use marijuana for whites, but was associated with increased risk of marijuana use among AIs. The latter finding is somewhat novel, given that past research has found that avoidance coping strategies are maladaptive for samples of white respondents (Baer et al, 1987; Richman et al, 2011) while being a protective factor for other racial minorities, such as African Americans (Richman et al, 2011; Van Gundy and Howerton, 2005). Our results lend further credence to the notion that the relationship between coping strategies and outcomes is much more nuanced and complex than has been suggested, with coping strategies being adaptive, maladaptive, or even of no import in predicting substance use behavior among adolescents.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations